The Relationship Between Occupational Noise Exposure and Work Fatigue Among Apron Workers at Tampa Padang Airport - Nurul Pratiwi Army; Annisa Suwahru; Astaman Sultan; Suci Setiani Annisa; Yusniar Anggraeny; Rizky Maharja; A. Mifta Farid Panggeleng; Bambang Hermawan (Sean Institute, 2026)
Work fatigue is a condition characterized by a decrease in work efficiency and physical endurance, with direct implications for workforce productivity and occupational safety. Apron workers at airports are simultaneously exposed to multiple occupational risk factors, most notably high levels of noise continuously generated by aircraft engines and ground support equipment operations. In addition to noise, age, workload, working hours, and length of service also influence the occurrence of work fatigue. This study analyzed the relationships between age, workload, working hours, length of service, and noise intensity with work fatigue among apron workers at Tampa Padang Airport, Mamuju. An observational analytic design with a cross-sectional approach was applied, conducted in January–February 2026. A total of 71 workers were selected through proportionate stratified random sampling from a population of 242. Work fatigue was measured using a reaction timer, workload via working pulse rate monitoring, and noise intensity using a sound level meter. Data on age, working hours, and length of service were collected through structured questionnaires. Univariate and bivariate analyses were performed using the chi-square test (α = 0.05). Results showed that 48 workers (67.6%) experienced work fatigue. Significant relationships were found between age (p = 0.001), workload (p = 0.001), working hours (p = 0.001), length of service (p = 0.001), and noise intensity (p = 0.017) with work fatigue. Management is advised to align working hours with regulatory standards and to enforce the mandatory use of hearing protection devices (earplugs/earmuffs) for all apron workers.